Pengaruh Fraud Hexagon Theory Terhadap Academic Fraud Mahasiswa Akuntansi - Anggrezola, Nathasya; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2026)
The purpose of this study was to determine how Fraud Hexagon Theory affects Academic Fraud of accounting students. There are 283 people were used to represent the entire population of accounting students from Universitas Negeri Padang, Universitas Andalas, Universitas Bung Hatta, Universitas Putra Indonesia "YPTK" Padang, Universitas Maritim Raja Ali Haji, and Universitas Mercu Buana Jakarta. This study used a simple random sampling technique and was limited by calculating the sample size using the slovin formula. This study used primary data in the form of questionnaires distributed via google form, with measurements using a 4-point likert scale. Multiple linear regression analysis was carried out in this research model. The results show that academic fraud among accounting students is influenced by 3 factors, namely stimulus, opportunity, and capability. However, this study shows that academic fraud among accounting students is not influenced by 3 factors, namely rationalization, ego, and collusion. Further research is expected to add other variables outside the variables in this study, and expand the population and sample.